Baseline Assessment on Women's Accessibility to Public Services (West Java Province) : Management Strengthening and Institution Building for Local Public Service and Providers - World Bank (Washington, DC, 2013)
The purpose of the baseline assessment is to provide baseline information on women access to public services, especially health, water, and population administration services. One of the objectives of decentralization is to improve the efficiency, effectiveness, quality, equity, accessibility, and responsiveness of public service delivery. Local governments in Indonesia still face a variety of barriers in addressing and improving public services and the welfare status and quality of life of the population. The assessment is intended to develop baseline information on women's accessibility to selected public services in Sumedang, Majalengka and Bandung Barat in the Province of West Java.